Israel, a journey of light. 5, A light to the nations - Tweedie, J. (John); Christians for Israel Canada; One Media (Firm); Exploration Films (Firm) ([United States] : Exploration Films, 2010)
Exploring the revived nation of Israel, Rev. Dr. John Tweedie marvels at the progress of a 'nation born in a day' barely more than 60 years ago. See and understand how Israel shines an exemplary democratic light within the Middle East.
DVD, all regions, NTSC, widescreen; Dolby Digital.
Title from container.
Host, Rev. Dr. John Tweedie.
Keywords: Israel -- History; Israel -- Church history; Documentary films; Nonfiction films; Religious films; Historical films